Acute oesophageal necrosis in multiple endocrine neoplasia type 1: an undescribed complication. Issue 1 (7th January 2021) - Bhattacharya, Sumona; Blau, Jenny E; Koh, Christopher
Abstract : Acute oesophageal necrosis (AEN) is a rare entity that most commonly presents as upper gastrointestinal bleeding. Complex pathophysiology may include oesophageal ischaemia as well as reflux of acidic gastric contents causing oesophageal mucosal injury. Management is supportive and directed at underlying comorbidities however prognosis is poor with complications such as oesophageal perforation, stricture and stenosis. Here we present the case of a 56-year-old man with multiple endocrine neoplasia type 1 (MEN1) and gastro-oesophageal reflux disease who developed AEN as a result of undiagnosed Zollinger-Ellison syndrome (ZES), duodenal ulcer-induced obstruction and hypotension from new-onset atrial fibrillation. AEN as the presentation of MEN1-associated ZES is an unusual presentation of this disease which clinicians, particularly endocrinologists and endoscopists, should be aware of.